Enzyme-assisted extraction of polyphenols from Sargassum mcclurei: antioxidant and alginate lyase inhibition activities - Nguyen, Thi Thuan; Vo, Mai Nhu Hieu; Nguyen , Vy Ha Nguyen; Pham, Duc Thinh; Le, Tuan Anh; Tran Xuan Thao, Tran Xuan Thao; Tran, Thi Thanh Van; Cao, Thi Thuy Hang (Vietnam Journal of Marine Science and Technology, 2025)
Sargassum mcclurei, a brown seaweed, is a rich source of bioactive polyphenols with promising applications in pharmaceuticals and functional foods. This study used enzyme-assisted extraction (EAE) method to enhance yield and bioactivity, followed by ethyl acetate fractionation. The total phenolic content (TPC) was quantified using the Folin-Ciocalteu method, and antioxidant activity was evaluated through total antioxidant capacity, DPPH radical scavenging, and Fe²⁺ chelation assays. The inhibitory effect on alginate lyase activity was assessed by measuring residual enzyme activity after incubation with polyphenol extracts. The ethanol extraction yielded 2.66% (w/w dry algae), while the ethyl acetate fraction accounted for 37% (w/w ethanol extract). The ethyl acetate fraction exhibited a higher TPC (499.61 ± 1.45 mg PGE/g extract) compared to the ethanol extract (303.04 ± 1.58 mg PGE/g extract) and demonstrated superior antioxidant activity (203.24 ± 1.47 mg AAE/g extract, IC50 = 30.38 µg/mL). Additionally, alginate lyase activity was inhibited dose-dependently, with a 40% reduction observed at 0.5 mg/mL of polyphenol extract. These results highlight the effectiveness of EAE in improving polyphenol yield and bioactivity. The strong antioxidant and enzyme inhibitory properties of S. mcclurei polyphenols suggest potential applications in oxidative stress management, microbial biofilm inhibition, and the development of natural therapeutics.